Academic Passion and its Relationship with Achievement Motivation among Students of Faculty of Educational Sciences at the Al al-Bayt University - Al-Adamat , Omar Atallah; Bani Khaled, Mohammed Soleiman (Dirasat: Educational Sciences, 2022)
Objectives: The present study aims to identify students’ levels of academic passion and achievement motivation considering the variables of gender, academic specialization and academic level in order to reveal the predictive power of academic passion in relation to achievement motivation. The study sample consisted of (350) male and female students chosen by availability. Methods: The study used the descriptive correlational method in the research, as two scales were used, academic passion scale, and achievement motivation through revealing the predictive ability of academic passion and motivation for achievement among students of the Faculty of Educational Sciences at Al-Bayt University. Results: The study’s findings demonstrated that the study group had a high level of harmonious passion. Despite a moderate amount of compulsive passion, considerable levels of achievement motivation were present. There were statistically significant gender-based differences favoring females in the level of harmonious passion, no differences resulting from academic specialty, and statistically significant academic level differences favoring third- and fourth-year students. Regarding the level of compulsive passion, the results showed no statistically significant differences by gender but did show differences related to academic specialization favoring special education specialization and differences related to academic level favoring first-year students. Moreover, the study results showed that compulsive and harmonious passions collectively explained 52.3% of the achievement motivation variance. Within this figure, compulsive passion explained 50.3% of the variance, while harmonious passion explained 1.9%. Conclusions: Based on the results, it is recommended to maintain the level of harmonious passion and achievement motivation among university students.